Improving Early Optics Instruction Using a Phenomenological Approach: A Field Study - Bitzenbauer, Philipp; Fliegauf, Kai; Sebald, Janika; Veith, Joaquin M.; Spiecker, Henrike (Optics, 2022)
Previous research has shown that phenomenological approaches in early optics education might be superior to traditional model-based instruction based on the light ray realm with regards to fostering students’ conceptual understanding of basic optics topics. However, it remains open to date which learning difficulties students encounter when being introduced to optics following a phenomenological approach—in particular, in comparison to the learning difficulties that are widespread among students introduced to optics via traditional model-based instruction. With this article, we contribute to closing this gap: We report the results of a quasi-experimental field study with N=189" role="presentation" style="max-height: none; display: inline; line-height: normal; font-size: 13.2px; overflow-wrap: normal; white-space: nowrap; float: none; direction: ltr; max-width: none; min-width: 0px; min-height: 0px; border-width: 0px; border-style: initial; color: rgb(34, 34, 34); font-family: Arial, Arial, Helvetica, sans-serif; position: relative;">N=189 secondary school students. We used ten items adapted from the literature in a pre-posttest design for an in-depth exploration of the conceptions of introductory optics topics acquired by N=89" role="presentation" style="max-height: none; display: inline; line-height: normal; font-size: 13.2px; overflow-wrap: normal; white-space: nowrap; float: none; direction: ltr; max-width: none; min-width: 0px; min-height: 0px; border-width: 0px; border-style: initial; color: rgb(34, 34, 34); font-family: Arial, Arial, Helvetica, sans-serif; position: relative;">N=89 students introduced to optics following a phenomenological teaching-learning sequence and compare these students’ conceptions to the ones acquired by N=100" role="presentation" style="max-height: none; display: inline; line-height: normal; font-size: 13.2px; overflow-wrap: normal; white-space: nowrap; float: none; direction: ltr; max-width: none; min-width: 0px; min-height: 0px; border-width: 0px; border-style: initial; color: rgb(34, 34, 34); font-family: Arial, Arial, Helvetica, sans-serif; position: relative;">N=100 peers who participated in traditional model-based instruction covering the same content topics. The results of this study substantiate earlier findings according to which phenomenological teaching might be a fruitful endeavour for early optics education, in particular, when it comes to teaching and learning about image formation by converging lenses.